The Speculative Solution to the Aporia of Temporality and the Meaning of Being - Lythgoe, Esteban (2025)
This paper explains the process by which Ricoeur applied the Aristotelian ontology of actuality and potentiality to his own hermeneutics, and how this development enabled him to find a speculative solution to the aporetics of time. I identify two alternative solutions within this process: the poetic solution presented in Time and Narrative and the speculative solution developed in Memory, History, Forgetting. Although the existential analytic plays a significant role in both solutions, I argue that the shift of perspective between these works was a result of the introduction of Spinoza’s concept of conatus.